2023
DOI: 10.3390/ijerph20126158
|View full text |Cite
|
Sign up to set email alerts
|

Developing an In-House Comprehensive Medication Review Training Program for Clinical Pharmacists in a Finnish Hospital Pharmacy

Abstract: Long-term continuing education programs have been a key factor in shifting toward more patient-centered clinical pharmacy services. This narrative review aims to describe the development of Helsinki University Hospital (HUS) Pharmacy’s in-house Comprehensive Medication Review Training Program (CMRTP) and how it has impacted clinical pharmacy services in HUS. The CMRTP was developed during the years 2017–2020. The program focuses on developing the special skills and competencies needed in comprehensive medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In HUS' earlier EHR system, it was easier to skip this step, which led to major discrepancies in the prior-to-admission/home medication list [53]. With the new EHR system, these errors are no longer hidden, and clinical pharmacists are a widely involved and appreciated resource for conducting medication reconciliations [10,54]. However, this more structured process is laborious, and the nationwide development of the Kanta system holding updated structured home medication lists in addition to electronic outpatient prescriptions [35] should be done urgently to save time and resources without risking medication safety [10].…”
Section: Medication Reconciliationmentioning
confidence: 99%
“…In HUS' earlier EHR system, it was easier to skip this step, which led to major discrepancies in the prior-to-admission/home medication list [53]. With the new EHR system, these errors are no longer hidden, and clinical pharmacists are a widely involved and appreciated resource for conducting medication reconciliations [10,54]. However, this more structured process is laborious, and the nationwide development of the Kanta system holding updated structured home medication lists in addition to electronic outpatient prescriptions [35] should be done urgently to save time and resources without risking medication safety [10].…”
Section: Medication Reconciliationmentioning
confidence: 99%
“…A systematic review presenting various tools and methods in oncology is reported by Whitman et al [19]. Interestingly, it can be implemented as part of research projects in Proactive Pharmacovigilance, or it can be a service of normal clinical practice exercised by structured health care personnel [20,21].…”
Section: Introductionmentioning
confidence: 99%